Clinical evidence for allergy in orofacial granulomatosis and inflammatory bowel disease. Issue 1 (15th August 2013) - Patel, Pritash; Brostoff, Jonathan; Campbell, Helen; Goel, Rishi M; Taylor, Kirstin; Ray, Shuvra; Lomer, Miranda; Escudier, Michael; Challacombe, Stephen; Spencer, Jo; Sanderson, Jeremy
Abstract: Background: Orofacial granulomatosis (OFG) causes chronic, disfiguring, granulomatous inflammation of the lips and oral mucosa. A proportion of cases have co‐existing intestinal Crohn's disease (CD). The pathogenesis is unknown but has recently been linked to dietary sensitivity. Although allergy has been suggested as an aetiological factor in OFG there are few published data to support this link. In this study, we sought clinical evidence of allergy in a series of patients with OFG and compared this to a series of patients with inflammatory bowel disease (IBD) without oral involvement and to population control estimates. Methods: Prevalence rates of allergy and oral allergy syndrome (OAS) were determined in 88 patients with OFG using questionnaires, skin prick tests, total and specific serum IgE levels. Allergy was also determined in 117 patients with IBD without evidence of oral involvement (79 with CD and 38 with ulcerative colitis (UC)). Results: Prevalence rates of allergy in patients with OFG were significantly greater than general population estimates (82% versus 22% respectively p = <0.0005). Rates of allergy were also greater in those with CD (39%) and, interestingly, highest in those with OFG and concurrent CD (87%). Conversely, whist OAS was common in allergic OFG patients (35%) rates of OAS were significantly less in patients with concomitant CD (10% vs 44% with and without CD respectively p = 0.006). Amongst CD patients, allergy was associated with perianal disease (p = 0.042) but not with ileal, ileocolonic or colonic disease location. Allergy in UC (18%) was comparable to population estimates. Conclusion: We provide compelling clinical evidence for the association of allergy with OFG whether occurring alone or in association with CD. The presence of gut CD increases this association but, conversely, reduces the expression of OAS in those with atopy. Interestingly, there is no evidence of increased allergy in UC.